2011
DOI: 10.1021/jm200718m
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Antimalarial Activity, and Structure–Activity Relationship of 7-(2-Phenoxyethoxy)-4(1H)-quinolones

Abstract: ICI 56,780 (5) displayed causal prophylactic and blood schizonticidal activity (ED50=0.05 mg/kg) in rodent malaria models but produced rapid acquisition of parasitological resistance in P. berghei infected mice. Herein we describe the synthesis of analogues of 5 with EC50 as low as 0.15 nM against multidrug resistant P. falciparum. Optimal activity with low cross-resistance indexes (RI) to atovaquone was achieved by introducing ortho-substituted aryl moieties at the 3-position of the 7-(2-phenoxyethoxy)-4(1H)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
44
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 23 publications
(55 reference statements)
0
44
0
Order By: Relevance
“…Salzer et al (11) found that endochin had liver and blood stage activity in avian malaria models; however, due to the lack of appropriate preclinical models, additional studies were not conducted (11). The compounds related to endochin also have activity against Plasmodium cynomolgi liver stages (12), and more recently, studies have shown these compounds to be potent in vitro and in vivo against Plasmodium falciparum and rodent malaria blood stage parasites (13)(14)(15)(16)(17)(18) …”
mentioning
confidence: 99%
“…Salzer et al (11) found that endochin had liver and blood stage activity in avian malaria models; however, due to the lack of appropriate preclinical models, additional studies were not conducted (11). The compounds related to endochin also have activity against Plasmodium cynomolgi liver stages (12), and more recently, studies have shown these compounds to be potent in vitro and in vivo against Plasmodium falciparum and rodent malaria blood stage parasites (13)(14)(15)(16)(17)(18) …”
mentioning
confidence: 99%
“…Therefore, we investigated the transmission-blocking activity of 4(1H)-quinolones that have activity against the blood and liver stages of parasites in the avian, rodent, and rhesus monkey malaria models (13)(14)(15). Recent studies have demonstrated that 4(1H)-quinolones are active against P. falciparum blood and liver stages in vitro (16)(17)(18)(19)(20)(21)(22)(23)(24)(25), as well as against P. berghei rodent malaria liver stages in vitro and in vivo (26).In this work, we tested three 3-alkyl-or 3-phenyl-4(1H)-quinolones (P4Qs; P4Q-95, P4Q-105, P4Q-146), one 7-(2-phenoxyethoxy)-4(1H)-quinolone (PEQ; ICI 56,780), and one 1,2,3,4-tetrahydroacridin-9(10H)-one (THA-93) (16,17,23) for their gametocytocidal, gametocidal, and sporozontocidal activity against P. falciparum as well as their transmission activities in vivo against P. berghei. These compounds were chosen because of their strong efficacy against blood stages in vitro (16,17,23).…”
mentioning
confidence: 99%
“…These compounds were chosen because of their strong efficacy against blood stages in vitro (16,17,23). We found that most of the compounds were not effective in killing early-and late-stage gametocytes, although they reduced or prevented male gametocyte exflagellation and subsequent vector infection in vitro and in vivo.…”
mentioning
confidence: 99%
See 2 more Smart Citations